Middle Fossa Approach for Resection of Vestibular Schwannomas: A Decade of Experience. Issue 2 (8th June 2018) - Kosty, Jennifer A; Stevens, Shawn M; Gozal, Yair M; DiNapoli, Vincent A; Patel, Smruti K; Golub, Justin S; Andaluz, Norberto O; Pensak, Myles; Zuccarello, Mario; Samy, Ravi N
Abstract: BACKGROUND: The middle cranial fossa (MCF) approach is a challenging surgical technique for the resection of small and intermediate sized, primarily intracanalicular, vestibular schwannomas (VS), with the goal of hearing preservation (HP). OBJECTIVE: To describe a decade-long, single institutional experience with the MCF approach for resection of VS. METHODS: This is a retrospective cohort study of 63 patients who underwent the MCF approach for resection of VS from 2006 to 2016. Audiometric data included pure-tone average (PTA), low-tone pure-tone average (LtPTA), word recognition score, and American Academy of Otolaryngology-Head and Neck Surgery (AAO-HNS) hearing classification at presentation and follow-up. Patients with postoperative serviceable (AAO-HNS class A-B) and/or useful (AAO-HNS class A-C) hearing were compared to those without HP. Facial nerve function was assessed using the House–Brackmann scale. RESULTS: The mean age and duration of follow-up were 50 ± 13 yr and 21 ± 21 mo, respectively. The mean tumor size was 10 ± 4 mm. The serviceable and usable HP rates were 54% and 50%, respectively. Some residual hearing was preserved in 71% of patients. Large tumor size ( P = .05), volume ( P = .03), and extrameatal tumor extension ( P = .03) were associated with poor audiometric outcomes. The presence of a fundal fluid cap ( P = .01) was a favorable finding. At definitive testing, LtPTA was significantly better preserved than traditional PTA ( P = .01). Facial nerve outcomes, tumor control rates, and durability of audiometric outcomes were excellent. 47% of patients pursued aural rehabilitation. CONCLUSION: In our series, the MCF approach for VS provided excellent rates of tumor and facial nerve function, with durable serviceable HP.